PREVALENCE OF ASYMPTOMATIC BACTERIURIA IN ANTENATAL WOMEN ATTENDING TERTIARY CARE HOSPITAL-A CROSS-SECTIONAL STUDY - SUBHASHINI, B. S. V. V.; VANI, T. M. S. S. SUDHA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Urinary tract infection (UTI) is one of the most common bacterial infections during pregnancy due to anatomical changes and physiological adaptations during pregnancy. Asymptomatic bacteriuria is the significant presence of bacteria in the urine of an individual without symptoms. Untreated asymptomatic bacteriuria (ASB) in pregnancy predisposes to symptomatic UTI in 25% of infected women. Screening of antenatal women help in early diagnosis and treatment of ASB and thus to prevent maternal and fetal morbidity and mortality. The present study was carried out to determine the prevalence of UTI in pregnant women and to study the bacteriological profile and antimicrobial sensitivity patterns of uropathogens. Methods: A Cross-sectional study was conducted for a period of six months and midstream urine specimens were collected from 480 pregnant females and were processed by standard protocols. All subjects were clinically identified to have no signs and symptoms of UTI. Antibiotic susceptibility testing was done as per CLSI guidelines. Results: Prevalence rate of asymptomatic bacteriuria was seen 10% in pregnant women. Majority of the culture-positive patients belonged to the age group of 26-30 y (31.25%). 70.84% were Gram-negative isolates and 29.16% were Gram-positive organisms. The commonest pathogen isolated was Escherichia coli (33.33%). In the present study, Extended Spectrum Beta-Lactamase (ESBL) production was seen in (20.58%) isolates, and Metallo Beta-Lactamase (MBL) production was seen in (17.64%) isolates. Conclusion: This study reveals the importance of screening of pregnant women for UTI. Emerging multi-drug resistance seen in uropathogens emphasizes the need to rationalize use of antibiotics, which eventually prevent development of resistant strains.